Climatology and trends of tropical cyclone high wind in mainland China: 1959–2011. Issue 24 (17th December 2015) - Ni, Xiang; Zhang, Qinghong; Ma, Ding; Wu, Liguang; Ren, Fumin
Abstract: The climatology and trends of tropical cyclone (TC) high wind (TCHW; wind speeds ≥10.8 m s −1 ) in mainland China during 1959–2011 were studied based on a comprehensive series of surface wind observations from 574 stations. Of these stations, 41 were affected by TCHW more than once per year and were mainly located along the southeast coastline or at some inland mountain locations. The contribution of TCHW frequency to high wind (HW; wind speeds ≥10.8 m s −1 ) frequency was highest along the southeast coastline of China and decreased rapidly at inland locations. Both the TCHW frequency (intensity) and HW frequency (intensity) displayed significant downward (weakened) trends after the 1980s. The proportion of HW events accounted for by TCHW decreased, although the trend was not significant. The changes in TCHW frequency and intensity were associated with variations in the number of influencing TCs (ITC: a TC that causes at least one TCHW event), ITCTs (ITC time: an observation time with ITCs), the range of ITC influence, and ITC intensity and track. The annual number of ITCs and ITCTs declined consistently during the study period. The range of ITC influence as related to the TC size in 1983–2011 was smaller than in 1959–1982. The variation of the percentiles of ITC intensity showed an increasing (decreasing) trend of weaker (stronger) ITCs. Years with the maximum TCHW frequency had more ITCs and ITCTs than those with the minimum TCHW frequency. Key Points: TCHW frequency in China displayed a significant downward trend after the 1980s The proportion of weak (strong) TCHW events increased (declined) from 1959 to 2011 TC number, track, intensity, and size are proved to be related to change of TCHW